2019
DOI: 10.1017/s0033291719000308
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and obesity, and their association with depression in relatively young people: findings from a large UK birth cohort

Abstract: BackgroundDepression frequently co-occurs with disorders of glucose and insulin homeostasis (DGIH) and obesity. Low-grade systemic inflammation and lifestyle factors in childhood may predispose to DGIH, obesity and depression. We aim to investigate the cross-sectional and longitudinal associations among DGIH, obesity and depression, and to examine the effect of demographics, lifestyle factors and antecedent low-grade inflammation on such associations in young people.MethodsUsing the Avon Longitudinal Study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 68 publications
(74 reference statements)
0
21
1
1
Order By: Relevance
“…Diabetes, metabolic disorder caused by insufficient insulin secretion or insulin utilization disorder. Studies have found that insulin deficiency or insulin resistance can also be observed in patients with depression ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes, metabolic disorder caused by insufficient insulin secretion or insulin utilization disorder. Studies have found that insulin deficiency or insulin resistance can also be observed in patients with depression ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperinsulinaemia is linked to the development of various chronic diseases including obesity, diabetes, CVD and some cancers (1)(2)(3) . It has been reported that hyperinsulinaemia is also involved in the pathophysiology of psychological disorders (4)(5)(6) . Coexistence of psychological disorders and diabetes might further highlight the role of hyperinsulinaemia in these conditions (7) .…”
mentioning
confidence: 99%
“…In addition to the direct effect of insulin on the nervous system, in recent years, some findings suggested that the association was related to the reduction of insulin receptor or the activity of receptor (ie, insulin resistance) in brain, 26‐28 and the insulin resistance was positively associated with depression 5 . Long‐term feeding of high‐fat diet induces peripheral insulin resistance.…”
Section: Insulin and Depressionmentioning
confidence: 99%
“…A survey has shown that about 30% of people with diabetes also suffer from depression and 10% have severe depression, which suggests a close relationship between the two diseases 1,2 . The mechanism of depression as a complication of diabetes is not completely clear, but studies have found that insulin deficiency or insulin resistance is the symptom that can also be observed in major depression disorder 3‐5 …”
Section: Introductionmentioning
confidence: 99%